Placing the entrepreneur in context : lessons from the leadership literature for Asia Pacific region / Peruvemba S. Jaya and Matthew H. Roy - S. Jaya, Peruvemba; Matthew, H. Roy (Faculty of Business and Management ; UiTM Press, 2000)
Traditional approaches to the study of entrepreneurship have viewed the entrepreneur in isolation - largely focusing on the traits necessary for success in these endeavors. This paper argues for a more contextual approach to defining and conceptually understanding the dynamics of entrepreneurship. Learning from the rich history of the leadership literature may prove invaluable to understanding the field of entrepreneurship. Specifically, insights from transformational leadership are used to broaden our understanding of entrepreneurship. Lessons for entrepreneurship scholars are highlighted in an attempt to move the field forward efficiently with particular attention given to Asian Pacific entrepreneurs and scholars